Risk attitudes and well-being in Latin America (2010)
A common premise in both the theoretical and policy literature on development is that people remain poor because they are too impatient to save and too risk averse to take the sort of chances needed to accumulate wealth. The empirical literature, however, suggests that this assumption is far from proven. We report on field experiments designed to address many of the problems confounding previous analyses of the links between risk preferences and well-being. Our sample includes more than 3,000 participants who were drawn representatively from six Latin American cities: Bogotá, Buenos Aries, Caracas, Lima, Montevideo, San José. In addition to the experiment which reveals interesting cross-country differences, participants completed an extensive survey that provides data on a variety of well-being indicators and a number of important controls. Focusing on risk preferences, we find little evidence of robust links between risk aversion and wellbeing. However, when we analyze the results of three treatments that add elements of reality to the decision problem, we see that these, more subtle, instruments correlate better with well-being, even after controlling for a variety of other important factors like the accumulation of human capital and access to credit.